Enterotisierung in Hölderlins Empedokles-Projekt - Roy, Priscilla Hayden (Revista Eletrônica Estudos Hegelianos, 2021)
While the development of the Empedocles’ figure in the various versions of Hölderlin’s drama has long been subject of scholarship, the shifts in the relationship between the hero and the women around him have remained largely unappreciated. These changes are anything but subtle: the woman close to him in the Frankfurter Plan is his “wife”; in the first draft Empedocles is unmarried, but is adored by a young woman, Panthea, who is not related to him; in the final draft, Panthea is transformed into his biological sister. The possibility of marital or erotic entanglements of the hero is thus continuously limited by each new phase in the course of the Empedocles’ project. This process, which I call “deserotization” here, is the subject of this text.